The impact of online negative word-of-mouth on consumers in the sports shoes industry - Barnabé, Andreia Filipa Venâncio Marujo (2018)
Nowadays social media platforms represent a great part of every person´s day to day. It is essential for every brand to follow this trend and to have a presence on these platforms in order to be closer to the customers. Facebook is one of the most famous and used social media platforms, and it can be a very important communication tool between the brand and the consumers. However, in some cases this communication tool can have a negative effect on the brands once consumers are increasingly using these platforms to make complaints about brands. The objective of this study is to analyse the effects of these complaints made by the consumers on Facebook brand pages on other customers who are exposed to this type of content. The study is focused on the sports shoes industry, and the effects are measured according to four constructs, brand attitude, perceived brand quality, negative word-ofmouth intentions, and re-patronage intentions. It is also included a moderator factor, so the effects are also studied according to the type of brand, namely economic or prestige brand. A questionnaire was applied to 421 individuals, with a Facebook account, and revealed that negative word-of-mouth intentions and re-patronage intentions were significantly influenced by the exposure to negative word-of-mouth. Also, revealed that the results are not different when a customer is exposed to NWOM regarding an economic brand or regarding a prestige brand.